Iceberg meltwater fluxes dominate the freshwater budget in Greenland's iceberg‐congested glacial fjords. Issue 21 (9th November 2016) - Enderlin, Ellyn M.; Hamilton, Gordon S.; Straneo, Fiammetta; Sutherland, David A.
Abstract: Freshwater fluxes from the Greenland ice sheet have increased over the last two decades due to increases in liquid (i.e., surface and submarine meltwater) and solid ice (i.e., iceberg) fluxes. To predict potential ice sheet‐ocean‐climate feedbacks, we must know the partitioning of freshwater fluxes from Greenland, including the conversion of icebergs to liquid (i.e., meltwater) fluxes within glacial fjords. Here we use repeat 0.5 m‐resolution satellite images from two major fjords to provide the first observation‐based estimates of the meltwater flux from the dense matrix of floating ice called mélange. We find that because of its expansive submerged area (>100 km 2 ) and rapid melt rate ( 0.1–0.8 m d −1 ), the ice mélange meltwater flux can exceed that from glacier surface and submarine melting. Our findings suggest that iceberg melt within the fjords must be taken into account in studies of glacial fjord circulation and the impact of Greenland melt on the ocean. Plain Language Summary: Over the last two decades, the volume of icebergs breaking‐off (i.e., calving) from the Greenland ice sheet has increased substantially. This increase has raised sea level and has potentially influenced the thermohaline ocean circulation that helps regulate the Earth's climate. Although ocean models can be used to estimate the impacts of increased iceberg calving on ocean circulation, the accuracy of these models depends on knowledge of the spatial distribution of the meltwater produced by Greenland's icebergs. In this paper we use iceberg size information from repeat satellite images to estimate the rates of iceberg melting and cumulative iceberg melt volumes in glacial fjords that connect two of Greenland's largest glaciers to the open ocean. We find that despite being previously overlooked by most scientific investigations of glacier‐ocean interactions, iceberg meltwater dominates these fjords' freshwater budgets throughout the majority of the year. We also find that up to 50% of iceberg volume is melted‐out by the time icebergs reach the open ocean. These results suggest that ocean models must take iceberg melting into account in order to accurately simulate changes in ocean circulation in response to increased iceberg production both now and in the future. Key Points: Freshwater fluxes from melting ice melange vary with submerged ice area and area‐averaged melt rate and can exceed 1000 m 3 /s Ice melange meltwater fluxes can dominate the freshwater budget of glacial fjords throughout the majority of the year Solid freshwater fluxes to the open ocean cannot be estimated from glacier discharge because up to 50% of iceberg mass is melted in fjords